Family Support in Relation to Future-Oriented Coping Among Research Scholars. (International Journal of Food and Nutritional Sciences, 2022)
Dealing with stress comes with more and more future-oriented processes whereby people anticipate and mobilise resources as they preempt future challenges. The current study was based on the Conservation of Resources theory and focused on the nature of the interaction between family support and future-oriented (proactive) coping in the case of Indian research scholars, who are vulnerable to chronic academic stress and uncertainty. Relied on a quantitative, cross-sectional design, the sample of the study comprised 80 research scholars aged between 25 and 40 years, who were enrolled in universities located in Kashmir to take part in the study using standardized self-report scales of family support and proactive coping. According to descriptive analyses, both perceived family support and proactive coping were relatively high. The Pearson correlation and regression results showed that family support and proactive coping had a significant positive relationship, and family support was a powerful predictor of proactive coping. Group comparisons also revealed that male scholars believed that they used more proactive coping than females, that older scholars had more perceived family support and higher patterned coping orientations; and no significant disparities were noted with respect to birth order. In general, the results have underlined the role of family support as an important psychosocial resource that enables anticipatory, goal-oriented coping in research scholars who navigate through strenuous academic settings. This paper highlights the significance of considering family-contextualization of institutional support services and intervention to enhance proactive coping, resilience, and persistence among scholars.